In vivo antioxidant properties of vitamin E and chromium in cold-stressed Japanese quails - Şahin, Nurhan; Şahin, Kazım; Onderci, M; Ozcelik, M; Smith, MO (Taylor & Francis Ltd, 2003)
An experiment was conducted to determine if vitamin E (alpha-tocopherol acetate) and chromium (chromium picolinate, Cr Pic) supplementation attenuate the negative effects of cold stress on egg production. egg quality. serum metabolites, and antioxidant status in Japanese quails (Coturnix coturnix japonica). One hundred and fifty laying Japanese quails (50-day-old) were divided into five groups, 30 birds per group. The laying quails kept at 6degreesC for 12 h/d (08.00 p.m. to 08.00 a.m.) were fed either a basal diet (low temperature-basal diet. CS group) or the basal diet supplemented with either 400 mug of Cr/kg of diet (Cr group), 250 mg of alpha-tocopherol-acetate per kg of diet (Vit. E group) or 400 mug of Cr plus 250 ing of alpha-tocopherol-acetate per kg of diet (Vit. E + Cr group) while quails kept at 18degreesC were fed a basal diet (thermo-neutral-basal diet, TN group). Performance and egg quality were significantly reduced in CS group compared with TN group. Supplemental chromium and vitamin E significantly increased live weight change, egg production, and improved feed efficiency in cold-stressed laying hens compared with the group fed the basal diet at 6degreesC. Egg production and egg weight were also greater (P < 0.05) in each supplemental group compared with the CS group. However, a combination of vitamin E and chromium, rather than each separately, provided the greatest performance. Supplemental vitamin E and chromium also increased serum vitamin C and E but, decreased malondialdehyde (MDA) concentrations (P < 0.05); the combination of vitamin E and chromium resulted in the highest levels of serum vitamin C and E within the cold-stressed quails. Results of the present study indicate that combined antioxidant supplements increased performance, egg quality and serum antioxidant levels while lowering MDA in cold-stressed quails.
Keywords: cold stress; chromium; vitamin E; egg production; Japanese quails